HYBRID MAXIMUMCONTROL STRUCTUREUSING FUZZY LOGICOF ELECTRIC VEHICLE - KRAA, O.; ABOUBOU, A.; AYAD, M.Y.; SAADI, R.; GHODBANE, H. (Courrier du Savoir; Vol. 17 (2013): Courrier du Savoir)
This paper presents a Modelling of traction control system of an Electric Vehicle (EV) based on the Energetic Macroscopic Representation (EMR) and the Maximum Control Structure (MCS). This last is using Fuzzy Logic Control(FLC) toinvert the EMR accumulation element for the control task. A developed combination of fuzzy control strategy with SMC combines the advantages of these two approaches and facilitates the inversion of the accumulation elements. In order to validate the simulation results, a comparison between the results obtained by MCS using IP controller which has already been developed by L2EP laboratory (Lille, France) and the presented MSC-FLC obtained by Matlab/Simulink software tool is included